Effects of post-mortem aging time and type of aging on palatability of low marbled beef loins. (February 2016) - Lepper-Blilie, A.N.; Berg, E.P.; Buchanan, D.S.; Berg, P.T.
Abstract: The study objective was to evaluate the effect of post-mortem aging period (14 to 49 days), dry vs. wet (D vs W) type of aging on the palatability of bone-in (BI) beef short loins (n = 96) and boneless (BL) strip loins (n = 96) possessing United States Department of Agriculture marbling scores between Slight and Small. Warner-Bratzler shear force (WBSF) scores decreased linearly over time (P = 0.0001). WBSF was not influenced by aging method or loin type. Aged flavor was higher for DBL than for DBI with WBL and WBI intermediate. Dry aging strip loins increase aged flavor yet did not improve beefy flavor compared to wet aging. Based on objective data and panelist's scores for tenderness, juiciness and aged flavor, a boneless, 28 days wet aged strip steak, cooked to 71 °C would provide the best combination of eating satisfaction and value. Highlights: Warner-Bratzler shear force scores decreased as aging period increased. Panelist tenderness scores increased as aging period increased. Aging period and method did not influence juiciness, beefy, and brown/roasted flavor. Regardless of aging period, method or type, steaks averaged less than 2.8 kg of WBSF and would be considered tender.